A p-type multi-wall carbon nanotube/Te nanorod composite with enhanced thermoelectric performance. Issue 16 (27th February 2018) - Park, Dabin; Ju, Hyun; Oh, Taeseob; Kim, Jooheon
Abstract : In this study, multi-walled carbon nanotube (MWCNT)/tellurium (Te) nanorod composites with various MWCNT contents are prepared and their thermoelectric properties are investigated. Abstract : In this study, multi-walled carbon nanotube (MWCNT)/tellurium (Te) nanorod composites with various MWCNT contents are prepared and their thermoelectric properties are investigated. The composite samples are prepared by mixing Te nanorods with surface-treated MWCNTs. Te nanorods are synthesized by solution phase mixing using polyvinylpyrrolidone (PVP). The MWCNTs used in this study are surface-treated with a solution consisting of H2 SO4 and HNO3 . With increasing MWCNT content, the composite samples exhibit a reduction in the Seebeck coefficient and enhanced electrical conductivity. The maximum power factor of 5.53 μW m K −2 is observed at 2% MWCNT at room temperature. The thermal conductivity of the composite reduced after the introduction of MWCNTs into the Te nanorod matrix; this is attributed to the generation of heterostructured interfaces between MWCNTs and the Te nanorods. At room temperature, the composites containing 2% MWCNTs exhibited the maximum thermoelectric figure of merit ( ZT ), which is ∼3.91 times larger than that of pure Te nanorods.